Insights of the Natural Reason in the Search for Truth (Athenagoras of Athens and His Attitude to Ancient Philosophy) - Vatashki, Atanas (Forum Theologicum Sardicense, 2025)
Atanas Vatashki, Insights of the Natural Reason in the Search for Truth (Athenagoras of Athens and His Attitude to Ancient Philosophy). The current paper explores the insights of the early Christian apologist Athenagoras of Athens regarding the rational foundations of theological knowledge. The author presents an original solution to the question of the relationship between faith and knowledge within the context of the early Christian writer’s work.